الرياضيات بالعربية

بين المتساويتين

ليكن $a,b \in \mathbb{N}^{*}$.
نقوم بالقسمة الأقليدية للعدد $a$ على $b$ : $a = bq + r \, , \quad 0 \leq r < b$, بين أن: $q = \text{E}\left( \frac{a}{b} \right)$

بين أن $\forall n,p,q \in \mathbb{N}^{*} \, : \quad \text{E}\left( \frac{\text{E}\left( \frac{n}{p} \right)}{q} \right) = \text{E}\left( \frac{n}{p q} \right)$
راجع الدرس : دالة الجزء الصحيح


لدينا القسمة الأقليدية للعدد $a$ على $b$ : $a = bq + r \, , \quad 0 \leq r < b$

وبالتالي $\frac{a}{b} = q + \frac{r}{b}$

لدينا $\text{E}\left( \frac{a}{b} \right) = \text{E}\left(q + \frac{r}{b}\right)$

بما أن $q \in \mathbb{N}$ فإن $\text{E}\left(q + \frac{r}{b}\right) = q + \text{E}\left( \frac{r}{b} \right)$

بما أن $0 \leq \frac{r}{b} < 1$ فإن $\text{E}\left( \frac{r}{b} \right) = 0$

إذن $q = \text{E}\left( \frac{a}{b} \right)$


ليكن $n,p,q \in \mathbb{N}^{*}$

نقوم بالقسمة الأقليدية للعدد $n$ على $p$, لدينا :

$n = p a + b \, , \quad 0 \leq b \leq p - 1$

حسب السؤال الأول لدينا $\text{E}\left( \frac{n}{p} \right) = a$

نقوم بالقسمة الأقليدية للعدد $a$ على $q$, لدينا :

$a = q c + d \, , \quad 0 \leq d \leq q - 1$

حسب السؤال الأول لدينا $\text{E}\left( \frac{a}{q} \right) = c$

وبالتالي لدينا : $\text{E}\left( \frac{\text{E}\left( \frac{n}{p} \right)}{q} \right) = c$

ولدينا $n = p (q c + d) + b = p q c + (p d + b)$

لدينا $0 \leq p d + b < pq - 1$

وبالتالي $\text{E}\left( \frac{n}{p q} \right) = c$

خلاصة : $\forall n,p,q \in \mathbb{N}^{*} \, : \quad \text{E}\left( \frac{\text{E}\left( \frac{n}{p} \right)}{q} \right) = \text{E}\left( \frac{n}{p q} \right)$